Antitumor Activity of VB-111, a Novel Antiangiogenic Virotherapeutic, in Thyroid Cancer Xenograft Mouse Models - Reddi, H. V. (SAGE Publications, 2011)
VB-111 is an engineered antiangiogenic adenovirus that expresses Fas-c in angiogenic blood vessels and has previously been shown to have significant antitumor activity in vitro and in vivo in Lewis lung carcinoma, melanoma, and glioblastoma models. To evaluate the efficacy of VB-111 in thyroid cancer, we conducted in vivo xenograft nude mouse studies using multiple thyroid cancer-derived cell lines models. VB-111 treatment resulted in 26.6% (P = 0.0596), 34.4% (P = 0.0046), and 37.6% (P = 0.0249) inhibition of tumor growth in follicular, papillary and anaplastic thyroid cancer models, respectively. No toxicity was observed in any model. All tumor types showed a consistent and significant reduction of CD-31 staining (P < 0.05), reflecting a reduction of angiogenic activity in the tumors, consistent with the intended targeting of the virus. A phase 2 clinical trial of VB-111 in patients with advanced differentiated thyroid cancer is ongoing.